Fundamentals of civil and criminal expertise in welfare and mistreatment syndrome in cattle - Amaral, Jackson Barros do; Tremori, Tália Missen; Batista, Ana Carolina Lopes; Hans, Elaine Jaqueline; Lisboa, Luísa de Oliveira (Pubvet, 2020)
Although little discussed and explored forensic investigation becomes an innovative and relevant demand for expertise in crimes of maltreatment against cattle. For the finding of crime, besides the low degree of well-being is also necessary to prove the intent by the agent. In the civil sphere, malpractice, recklessness and neglect are known as modalities of guilt or expression of wrongdoing and the transgressions resulting from these grounds present as an elementary cause, sometimes lacking the conscience of the offender. Lawsuits related to cattle are rare, although in recent times they tend to increase and professional errors in health care and reproduction, which are linked to civil liability, are controlled by the Consumer Protection Code (CDC) and the Civil Code. In addition, veterinarians are still subject to supervision of their professional conduct in accordance with the Veterinary Doctor's Code of Ethics (CEMV). The aim of this article is to discuss the principles and fundamentals of Forensic Veterinary Medicine in conducting expertise and examination of body of crime as necessary requirements for the preparation of expert report, especially in cases of maltreatment in cattle. In addition to proposing a specific protocol for welfare assessment in cattle as an auxiliary tool in the preparation of expert reports. Given the above, the veterinarian should be careful in preparing individual patient and herd records, taking ethical attitudes and making a commitment to animal welfare.
Keywords: animal welfare; cattle production; criminalistic; corpus of delicti; veterinary expertise